Schematic Design Process in Block Plan Building Industrial Block in Gianyar-Bali - Dinata, Aswin Pandu; Paturusi, Syamsul Alam; Budjana, I Gusti Bagus (Journal of A Sustainable Global South, 2017)
Plastic waste is now a common thing happening in the community so that it becomes a major problem in environmental pollution. The growing population and changing lifestyle of society led to the ever increase volume of plastic waste are generated every day. Please note that the plastic waste is inorganic waste that can not be broken down by bacteria, even if dumped in any place, the plastic waste takes long times until the plastic waste is destroyed by itself because of the influence of air temperature or climate. It is not good if the processing of plastic waste is done by way of burnt be-cause it may cause air pollution which is harmful to living beings and the environment. Therefore, it would be nice if the plastic waste can be reuse through the processing of ore into plastic or made into new products in the form of a craft that is more usable and valuable. Processing of plastic waste that is done well can aid in the reduction of the number of plastic waste, so it is needed a design of Industrial plastic waste as the place of processing plastic waste. As for the de-sign of this facility beginning with the stages of the design process as the initial schematic in deciding the block plan of the building. Schematic design can be use as a reference in the design process because it includes design ideas. Index Terms — industry, plastic waste, environment.